God-images and politics: the contribution of Trinitarian theology - Deetlefs, Johannes Petrus (University of the Free State, 2018)
The aim of this study is to determine whether Trinitarian theology could contribute positively towards the dialectical relationship between God-images and politics. The central question is, “In what way can the Trinitarian confession be related to the political dimension of society?” That God-images influence the political environment in which humans live their lives has been established through various studies. It is also generally accepted that a person’s God-image develops through various stages and, once formed, does not remain static but is fluid and changes with time as a result of his or her experience and gaining of additional knowledge. Interaction with other important persons in their lives, as well as religious education, affect the formation of God-images. Ethnic and social background also play a role in the development of a person’s God-image. The political nature of God-images is an indisputable fact. Changes in God-images are often followed by changes in the political structures within societies. Strict monotheism, where God is perceived as a solitary singe-person, has often in the past been employed for the justification of authoritarianism and hierarchy. It is argued that the one supreme ruler in heaven is represented on earth by one supreme ruler. It has been claimed that such a strict monotheism has promoted religious violence against the other who holds different convictions than those promulgated by the ruler. The twentieth-century Trinitarian renaissance has emphasized the relationality of the Divine. This new awareness of the doctrine of the Trinity and its practical implications for human existence, together with the move from a substance ontology to a relational ontology, has initiated a number of studies which concentrate on the relevance of the Trinity for social ethics. The biblical foundation of the doctrine has been placed under a microscope again as theologians started to realize the importance of this fundamental doctrine for Christian faith and life. The new emphasis on the Trinity started by Hegel was continued by theologians such as Barth and Rahner, and in their wake a number of prominent theologians have continued the discourse on the Trinity, with some exciting developments. One of the developments that has significance for the church’s understanding of the triune nature of God is the development of a social Trinity. Theologians such as Moltmann, Boff, Johnson and LaCugna, influenced by Zizioulas’ concept of personhood as relational, articulated the concept of a social Trinity. Interestingly, this move towards social Trinitarianism has mostly left an older generation of South African theologians unaffected, while it was picked up by the younger generation and incorporated into their theology. The move towards a relational Trinity and the emphasis on the practical relevance of the Trinity have been questioned by some scholars who caution that the difference between the Divine and human persons is just too significant. Prominent critics of the social Trinity and its correlation with society are, among others, Tanner, Kilby and Holmes. They reject the possibility of imitation of the Trinity and Tanner suggests participation in the life of the Trinity through Christ instead. The position taken in this study is that both imitation and participation are valid options with biblical justification and that the dichotomy, where one is set against the other, is the wrong approach towards addressing the problem. Humans are created in the image of God and should therefore reflect something, however vaguely, of God’s life in Trinity. Through Christ believers are drawn into the life of the Trinity and participate in the Divine community, while they are also commanded in the Bible to imitate the actions of mercy and righteousness of the triune God. The quality of the Trinitarian relationality could very well be reflected within society.

Die doel van hierdie studie is om vas te stel of 'n Trinitariese teologie 'n positiewe bydrae kan lewer tot die dialektiese verhouding tussen godsbeelde en politiek. Die sentrale vraag is “Op watter wyse kan die Trinitariese belydenis verbind word met die politieke dimensie van samelewings?” Verskeie studies het aangetoon dat die politieke klimaat waarin mense leef hul godsbeelde beïnvloed. Verder word algemeen aanvaar dat 'n person se godsbeeld deur verskeie stadia ontwikkel en nie staties is nie, maar buigsaam, sodat dit verander met tyd en deur ondervinding. Die interaksie met ander belangrike persone, sowel as godsdiensonderrig, is ook bepalend vir die ontwikkeling van godsbeelde. Etnisiteit en sosiale agtergrond speel ook 'n belangrike rol in die vorming van 'n persoon se godsbeeld. Die feit dat 'n persoon se godsbeeld politieke betekenis het word wyd aanvaar en 'n verandering in 'n samelewing se godsbeeld lei dikwels tot 'n verandering in politieke strukture. Streng monoteïsme, waar daar aan God gedink word as 'n enkelvoudige persoon, is dikwels in die verlede aangevoer ter ondersteuning van outokratiese en hiërargiese samelewings waarin die een hemelse regeerder op aarde verteenwoordig word deur die een monargiese regeerder. Dit word beweer dat so 'n streng monoteïsme dikwels godsdienstige geweld teenoor andersdenkende persone tot gevolg het. Die Trinitariese renaissance gedurende die twintigste eeu het opnuut die relasionele karakter van God beklemtoon. Hernude bewustheid van die belangrikheid van die Triniteit en die praktiese waarde daarvan, asook die verskuiwing vanaf 'n substansiële na 'n relasionele ontologie, het gelei tot 'n aantal studies oor die belangrikheid van die Triniteit vir die sosiale etiek. Die bybelse grondslag van die leer van die Triniteit is opnuut ondersoek. Hegel se beklemtoning van die belangrikheid van die Triniteit is verder gevoer deur teoloë soos Barth en Rahner en 'n aantal prominente teoloë wat hulle opgevolg het, met opwindende ontwikkelings in die Godsleer. Die ontwikkeling van 'n sosiale Triniteit hou belangrike gevolge in vir die kerk se begrip van die wese van die drie-enige God. Onder invloed van Zizioulas se konsep van persoon in gemeenskap met ander, het teoloë soos Moltmann, Boff, Johnson en LaCugna die leer van 'n sosiale Triniteit ontwikkel. Interessant genoeg, het die ontwikkeling van 'n sosiale Triniteitsleer 'n ouer geslag Suid-Afrikaanse teoloë geensins beïnvloed nie, en sou dit die jonger geslag teoloë wees wat die waarde daarvan ontdek en opneem in hul teologiese werk. Die verskuiwing na 'n relasionele Triniteit en die beklemtoning van die praktiese implikasies daarvan is egter deur sommige teoloë bevraagteken. Hulle waarsku dat die verskille tussen die goddelike persone en mense die imitasie van die Triniteit onmoontlik maak. Tanner, Kilby en Holmes, onder andere, is van die belangrikste kritici wat enige imitasie van die Triniteit verwerp. Tanner stel voor dat partisipasie 'n meer geskikte weg is om te volg. In hierdie studie word van die standpunt uitgegaan dat beide imitasie en partisipasie geldige benaderings is en dat die afspeel van die een teen die ander onnodig is. As geskape na die beeld van God behoort die mens iets, hoe vaag ookal, van die gemeenskap van die Trinitariese persone te weerspieël. Deur Christus kry gelowiges deel aan die gemeenskap wat die lewe van die Triniteit uitmaak, terwyl hulle terselfdertyd in die Bybel beveel word om ook die dade van barmhartigheid en geregtigheid van God na te boots. Dit is moontlik dat die kwaliteit van die Trinitariese relasionaliteit in die samelewing weerspieël kan word.
Thesis (D.Phil. (Historical and Constructive Theology))--University of the Free State, 2018
Keywords: Empire; God-image; Imagination; Imitation; Participation; Perichoresis; Personhood; Politics; Relationality; Religious Symbols; Social Trinity; Trinitarian; Trinity